Antibacterial Cotton Fabric Functionalized with Copper Oxide Nanoparticles - Roman, Luz E. (2020)
Textiles functionalized with cupric oxide (CuO) nanoparticles have become a promising option to prevent the spread of diseases due to their antimicrobial properties, which strongly depend on the structure and morphology of the nanoparticles and the method used for the functionalization process. This article presents a review of work focused on textiles functionalized with CuO nanoparticles, which were classified into two groups, namely, in situ and ex situ. Moreover, the analyzed bacterial strains, the resistance of the antimicrobial properties of textiles to washing processes, and their cytotoxicity were identified. Finally, the possible antimicrobial mechanisms that could develop in Gram-positive and Gram-negative bacteria were described.